TINJAUAN MASHALIH AL-MURSALAH TERHADAP IDAH SUAMI MENURUT SURAT EDARAN DIRJEN BIMAS ISLAM NOMOR P-005/DJ.III/HK.00.7/10/2021 - Salman Fattah; Muammar M. Bakry; Abd. Rauf Muhammad Amin (Universitas Islam Negeri Alauddin Makassar, 2025)
This study discusses the concept of 'iddah for men (syibh al-iddah) based on the Circular Letter of the Director General of Islamic Community Guidance (Dirjen Bimas Islam) No. P-005/DJ.III/HK.00.7/10/2021 concerning Marriage During a Woman's 'Iddah Period. The research is analyzed through the maslahah al-mursalah approach, which explores aspects of benefit (maslahah), ease, and the prevention of harm (dharar). The concept of 'iddah for men is not explicitly regulated by definitive (qath’i) scriptural texts, making the istislahi method relevant for legal reasoning (istinbath al-hukm). The objective of this study is to examine how maslahah al-mursalah views 'iddah for men, based on the aforementioned circular. This research is qualitative in nature, using a library research approach with a descriptive-analytical method. The findings indicate that 'iddah for men provides benefits to both former husbands and wives, even though there is no explicit (qath’i) command in the Qur'an or the Hadith of the Prophet (peace be upon him) regarding it. Thus, the study concludes that the implementation of 'iddah for men, as outlined in the circular, is obligatory based on maslahah considerations, in order to prevent potential harm (dharar).